PERFORMANCE EVALUATION OF NEEM POWDER-BASED FILTERS FOR HOUSEHOLD-LEVEL DEFLUORIDATION - Lamb, Prasad Balbhim; Sadgir, Parag; Awsarmal, Prashant (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Fluoride contamination in drinking water has emerged as a critical public health concern, especially in rural and semi-urban regions of India. This study investigates the efficiency of Azadirachta indica (Neem) powder-based filters for household-level defluoridation of water. Using experimental setups and comparative analysis, the adsorptive performance, removal efficiency, sustainability, and cost-effectiveness of Neem powder were evaluated. Results show that Neem powder has significant fluoride adsorption capacity, making it a viable eco-friendly alternative to commercial defluoridation techniques. The study recommends further research on enhancing filter design and scaling for community use.